All-fiber mode-locked laser emitting broadband-spectrum cylindrical vector mode. (March 2020) - Tao, Runxia; Li, Hongxun; Zhang, Yimin; Yao, Peijun; Xu, Lixin; Gu, Chun; Zhan, Qiwen
Highlights: A broadband mode conversion over 120 nm at 1.0 μm is realized. A output coupler with broadband reflection is utilized. Cylindrical vector beam pulse with high purity and broadband can be generated. Abstract: We experimentally demonstrate an all-fiber mode-locked laser emitting broadband-spectrum cylindrical vector mode pulse based on nonlinear polarization rotation and long-period fiber grating. In this laser, A few-mode long-period fiber grating with broad bandwidth of 125 nm at 1.0 μm band is utilized as mode converter inside the cavity. A flat-end connector deposited with gold film is used as output coupler offering a wideband reflection. Thus the generation of broadband spectrum cylindrical vector mode is feasible owing to the combination of broadband mode converter and output coupler. Stable mode-locked train is achieved at a repetition rate of 9.83 MHz and pulse duration of 168 ps. The proposed laser oscillates at 1030 nm with a broad spectral width of 5 nm at 3 dB. All four degenerate vector modes in the first group higher-order mode can also be obtained with mode purity higher than 95%. This work may have the potential for generation of high-purity and ultra-fast cylindrical vector beam.